Lateral Flow Immunoassay for Visible Detection of Human Brucellosis Based on Blue Silica Nanoparticles - Ge, Lirui; Wang, Dan; Lian, Fengnan; Zhao, Jinbin; Wang, Yue; Zhao, Yuyi; Zhang, Lanting; Wang, Juan; Song, Xiuling; Li, Jinhua; Xu, Kun (Frontiers in Veterinary Science, 2021)
Brucellosis is a highly contagious zoonosis chronic infectious disease which retained a strong latent capability to menace human’s health and economic development by direct or indirect ways. However, the existing methods of brucellosis diagnosis are time-consuming and expensive as they require tedious experiment procedure, sophisticated experimental device and performance. To overcome these defects, it is truely necessary to establish a real-time, on-site and rapid detection method for the human brucellosis. Here, a lateral flow immunoassay (LFIA) which possessed rapid, sensitive, alternative and degree of accuracy diagnosis procedure for human brucellosis was developed based on blue silica nanoparticles (SiNPs), Staphylococal protein A (SPA), surface Lipopolysaccharide of Brucella spp.(LPS) which can be applied for rapid and feasible detection of human brucellosis. As far as we known, using blue SiNPs as signal probe of LFIA for rapid diagnosis of human brucellosis is the first report. The precursor of blue SiNPs@SPA such as colorless SiNPs and blue SiNPs are synthesized at first, then coupled SPA into the suface of blue SiNPs by covalent bond to prepared blue SiNPs@SPA as capture signal to catch the antibody in brucellosis positive serum, When SPA combined with the antibodies in brucellosis positive serum, it will be captured by LPS on test line forming Antigen-antibody sandwich structure resulting T-line turn to blue. Finally, the results showed that it is convincing to used blue SiNPs as the visible labels of LFIA and standard brucellosis serum (containing Brucella spp. antibody at 1000 IU/mL) could be detected for a dilute to 10-5 and detection limit of this method was 0.01 IU/mL. Besides that, it also demonstrated good specificity and accuracy for the detection of real human serum samples. Above all, a blue SiNPs-based LFIA that we have developed, provides a rapid, highly accurate and cheap on-site diagnosis of human brucellosis, as well as shows great promising latent capability in clinical diagnostics for other diseases.